The indirect relationship between sleep and cognition in the PREVENT Cohort: Identifying targets for intervention - Tari, B; Yehuda, MB; Laurell, AAS; Ritchie, K; Dauvilliers, Y; Ritchie, C; Lawlor, B; Naci, L; Terrera, GM; Malhotra, PA; Watermeyer, T; Dudas, R; et al. (2023)
Introduction As the global population ages, the economic, societal, and personal burdens associated with worsening cognition and dementia onset are growing. It is therefore becoming ever more critical to understand the factors associated with cognitive decline. One such factor is sleep. Adequate sleep has been shown to maintain cognitive function and protect against the onset of chronic disease, whereas sleep deprivation has been linked to cognitive impairment and the onset of depression and dementia.